PENGARUH CORPORATE FINANCIAL PERFORMANCE TERHADAP STOCK RETURN: ANALISA PADA PERUSAHAAN YANG TERDAFTAR DI INDONESIA STOCK EXCHANGE - Juan Carlos Pangestu (Jurnal Penelitian Akuntansi (JPA), 2021)
This study purpose to examine and analyze the effect of corporate financial performance proxied by the variables Return on Equity, Earnings per Share, and net profit margin, on Stock Return. This study uses secondary data, the sample in this study are companies listed in the SRI-KEHATI stock index on the Indonesia Stock Exchange for the period 2017 – 2019. The number of companies that are sampled are 15 companies with an observation period of 3 years and using the purposive sampling method. The method of analysis in this study is panel data regression analysis using the SPSS program. Hypothesis testing uses a significance level of 5%. The results of the classical assumption test are that the data is normally distributed, and there is no multicollinearity, no Heteroscedasticity, and no Autocorrelation. The results of this study indicate that Earnings per share (EPS) and Net Profit Margin (NPM) have a significant effect on Stock Return. Meanwhile, Return on Equity (ROE) has no effect on Stock Return.